Impact of Social Media Marketing Activities and ESG Disclosure on Brand Building: A Mediating Role of Customer Engagement - Rajbanshi, Pratibha; Shrestha, Swornim; Pradhan, Annanya; Shrestha, Dipasa; Khadka, Nisha; Thakur, Ritesh Kumar (New Perspective: Journal of Business and Economics, 2025)
This study examines the impact of Social Media Marketing Activities (SMMAs) and Environmental, Social, and Governance (ESG) disclosure on brand building in Nepal's e-commerce sector, with customer engagement as a mediator. Focusing on urban markets like Kathmandu, Lalitpur, and Bhaktapur, the research analyzes how marketing practices affect brand perception, loyalty, and trust. The SMMAs studied include Ratings and Reviews, Promotional Activities, Influencer-Generated Content, and User-Generated Content, while ESG disclosure emphasizes transparency, sustainability, and ethical governance. Primary data from 130 respondents were collected through structured questionnaires and analyzed using regression and mediation techniques. Findings show customer engagement significantly mediates the relationships between both SMMAs and ESG disclosure with brand building. Promotional Activities, User-Generated Content, and ESG disclosure have a notable positive effect on brand building, whereas Ratings and Reviews and Influencer-Generated Content do not. These insights suggest that personalized and interactive social media strategies foster stronger emotional connections, enhancing brand loyalty. The research underscores the strategic role of ESG initiatives combined with targeted social media marketing in gaining a competitive edge in Nepal’s growing digital economy. The study offers practical implications for e-commerce platforms seeking to strengthen brand identity and customer relationships, and suggests future research expand geographically and methodologically for deeper insights.